The next generation of passive optical networks: A review. (May 2016) - Abbas, Huda Saleh; Gregory, Mark A.
Abstract: Passive Optical Networks (PONs) have become a popular fiber access network solution because of its service transparency, cost effectiveness, energy savings, and higher security over other access networks. PON utilizes passive low-power components which removes the need for power-feeding in the fiber distribution network. This paper presents three different generations of PON that are based on the Ethernet PON and Gigabit PON standards. This article showcases the first generation of PON in terms of physical and data link layers and forms the basis for discussion about the different approaches being pursued for the next generation stage 1 PON (NG-PON1). Additionally, the main objective of this study is to review the technologies proposed for the next generation stage 2 PON (NG-PON2); highlighting the important contributions and limitations of the corresponding technologies. Hybrid approaches that combine multiple technologies are introduced as a solution to eliminate major limitations and to improve overall system-wise performance. However, NG-PON2 is still suffering from a number of challenges include cost, reach, capacity and power consumption are discussed at the end of this paper. Another purpose of this paper is to identify potential remedies that can be investigated in the future to improve the performance of the NG-PON2.